Synthesis and characterization of poly(methyl methacrylate)-b-polysryrene by click chemistry reaction - Anith Liyana Mohd. Sis, 1988-; Md. Nasir Katun; Fakulti Sains (2010)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2010